2017
DOI: 10.1590/1678-4162-9069
|View full text |Cite
|
Sign up to set email alerts
|

Inoculação de proteína isolada de soja em ovos embrionados oriundos de matrizes semipesadas com diferentes idades

Abstract: Inoculação de proteína isolada de soja em ovos embrionados oriundos de matrizes semipesadas com diferentes idades

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Once the homogenization management of incubated eggs is adopted, it is naturally expected that the egg weight will not show significant changes, but the supplementation of the oils could affect the weight of the chick at birth, as already recorded in a previous study conducted by Damasceno et al (2017), this fact not observed in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 69%
“…Once the homogenization management of incubated eggs is adopted, it is naturally expected that the egg weight will not show significant changes, but the supplementation of the oils could affect the weight of the chick at birth, as already recorded in a previous study conducted by Damasceno et al (2017), this fact not observed in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 69%
“…Our results pointed that the use of IOF increased the hatchability (IOF Control and at 0.5% L-glutamine) and the development of the gastrointestinal tract, attributing these results to the increase in available nutrients to the chicks during the embryo development. Based on positive preliminary studies using amino acids and proteins (Pedroso et al, 2006;Damasceno et al, 2017), the first objective of IOF is to increase the concentration of available nutrients and improve the embryo development of chicks (Foye et al, 2007). However, Damasceno et al (2017) reported that high levels of substances using to IOF may cause a gradual reduction in hatchability, and a subsequent increase in embryo mortality, especially the intermediary embryo mortality (shortly after inoculation).…”
Section: Discussionmentioning
confidence: 99%
“…Based on positive preliminary studies using amino acids and proteins (Pedroso et al, 2006;Damasceno et al, 2017), the first objective of IOF is to increase the concentration of available nutrients and improve the embryo development of chicks (Foye et al, 2007). However, Damasceno et al (2017) reported that high levels of substances using to IOF may cause a gradual reduction in hatchability, and a subsequent increase in embryo mortality, especially the intermediary embryo mortality (shortly after inoculation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauric acid, in turn, is abundantly found in coconut oil and has immunological activities, which are described in several studies as antiviral, antibacterial, and anti-protozoan properties (Donaldson, Madziva, & Erlwanger 2016). The nutritional management of a diet can act as a modulator to produce specific responses, naturally strengthen immunity, and thus improve the performance of birds in the face of health challenges present in the breeding system (Damasceno et al, 2017). According to Pinto et al (2014), the current interests revolve around n-3 fatty acids that can act by inhibiting the synthesis of inflammatory mediators derived from achydodon acid.…”
Section: Introductionmentioning
confidence: 99%